Relationship between clinical grade, cerebral blood flow, and electroencephalographic alterations in patients with chronic subdural hemorrhage - Kaplan, Metin; Berilgen, Mehmet Said; Erol, Fatih S.; Artas, Hakan; Serhatlioglu, Selami; Ozveren, Mehmet Faik (Lippincott Williams & Wilkins, 2006)
Objective: To analyze the correlation between clinical grading, brain blood flow. and electroencephalographic (EEG) changes in cases with chronic subdural hemorrhage (CSH). Material and Methods: Thirteen patients with unilateral CSH, who were treated in our clinic were selected. The preoperative peak systolic flow rate, mean flow rate, end-diastolic flow rate, resistive index, and pulsatility index (PI) of both middle cerebral arteries (MCA) were recorded in all participants by transcranial Doppler. In addition, EEGs of all cases were evaluated. Results: Classification of the hemorrhage as hypodense, isodense, and mixed type by computed tomography scanning was not correlated with the brain blood flow. In cases with clinical grade 2 hemorrhage, the flow rate of the ipsilateral MCA was decreased. On the other hand, the ipsilateral PI had increased in the same cases. The thickness of the hemorrhage was below 2 cm in all patients with a normal EEG. The PI value was high in patients with an abnormal EEG. Conclusions: The blood flow rate of the MCA on the hemorrhagic side in cases with CSH is lower than that of the contralateral artery. However, this decrease does not have a linear correlation with the thickness of the hemorrhage or clinical arade. The increase in the ipsilateral PI is more significant than the decrease in the MCA blood flow rate in determining the clinical grade. This suggests that hemorrhage should have an impact that is adequate to activate compensatory mechanisms to observe changes in the EEG recordings.
Keywords: chronic subdural hemorrhage; brain blood flow; EEG